Alternative factor specifications, security characteristics, and the cross-section of expected stock returns1We are especially grateful to Eugene Fama (a referee), an anonymous referee and Bill Schwert (the editor) for insightful and constructive suggestions. We also thank Wayne Ferson, Ken French, Will Goetzmann, Craig Holden, Ravi Jagannathan, Bob Jennings, Bruce Lehmann, Josef Lakonishok, Richard Roll, participants at the 1997 Meetings of the Western Finance Association, the 1997 UCLA/USC/UC Irvine conference, the November 1997 Asset Pricing Meeting of the National Bureau of Economic Research, the Atlanta Forum, and seminars at Columbia, Indiana, Florida, New York, Tulane, and Yale Universities; Eugene Fama and Ken French for providing part of the data used in this study; and Christoph Schenzler for excellent programming assistance. The second author acknowledges support from the Dean's Fund for Research and the Financial Markets Research Center at Vanderbilt University. We are responsible for remaining errors. This paper was formerly titled `A Re-Examination of Security Return Anomalies'.1 - Brennan, Michael J.; Chordia, Tarun; Subrahmanyam, Avanidhar (Journal of Financial Economics, 1998)
We examine the relation between stock returns, measures of risk, and several non-risk security characteristics, including the book-to-market ratio, firm size, the stock price, the dividend yield, and lagged returns. Our primary objective is to determine whether non-risk characteristics have marginal explanatory power relative to the arbitrage pricing theory benchmark, with factors determined using, in turn, the Connor and Korajczyk (CK; 1988) and the Fama and French (FF; 1993b) approaches. Fama–MacBeth-type regressions using risk adjusted returns provide evidence of return momentum, size, and book-to-market effects, together with a significant and negative relation between returns and trading volume, even after accounting for the CK factors. When the analysis is repeated using the FF factors, we find that the size and book-to-market effects are attenuated, while the momentum and trading volume effects persist. In addition, Nasdaq stocks show significant underperformance after adjusting for risk using either method.